1971
DOI: 10.1149/1.2407892
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Properties of Anodic Oxide Films of Ta, Nb, Zr, Ti, W, and V Formed by the Ion-Cathode Method

Abstract: Amorphous oxide films have been grown on Zr, Ti, W, Ta, Nb, and V by ionized gas anodization using the ion cathode as a source of negative ions. Films were grown on each metal at constant current to 175V followed by constant voltage for about 4 hr. Several electrical and optical properties were measured for the anodic films produced on these refractory metals. Resistivities of the anodic oxide films on Zr, Ti, W, Ta, Nb, and V ranged from 1014 to 1017 ohm‐cm. Breakdown voltages with the refractory metal positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1972
1972
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…3-9 and the preceding papers cited in Ref. [4][5][6][7][8][9]. Compared with the works on O2 reduction kinetics, few studies have reported the electrode reaction in compound-gas atmospheres.…”
Section: Kensuke Isobe Motoaki Tajika Ikumasa Koshiro Hideki Maruymentioning
confidence: 99%
“…3-9 and the preceding papers cited in Ref. [4][5][6][7][8][9]. Compared with the works on O2 reduction kinetics, few studies have reported the electrode reaction in compound-gas atmospheres.…”
Section: Kensuke Isobe Motoaki Tajika Ikumasa Koshiro Hideki Maruymentioning
confidence: 99%
“…In addition, highly polarizable oxide dielectrics are generally characterized by considerably high dielectric losses, 15 which also increase with the conductivity in a particular material. 16 All transition metal oxides would be insulating dielectrics if the perfect stoichiometry were obtained. However, achievement of the ideal stoichiometry corresponding to the fully oxidized metals is complicated during low-temperature film deposition processes.…”
mentioning
confidence: 99%
“…In this paper we would like to report on an ellipsometric study of the plasma oxidation of tantalum. Since the pioneering work of Miles and Smith (1) on the formation of oxides in an oxygen glow discharge there have been several studies of the plasma oxidation of tantalum (2)(3)(4). One of the main problems with these earlier studies has been the technique used to measure the oxide thickness.…”
mentioning
confidence: 99%